2013
DOI: 10.1055/s-0033-1360460
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the Treatment of Pediatric Long Bone Shaft Fractures

Abstract: Shaft fractures of the long bones are among the most common pediatric injuries. They are characterized by a limited potential for spontaneous correction because of the fractures--distance to the physis. Although conservative treatment has been practiced for many years with satisfying results, several aspects have led to an increase in the numbers of surgical procedures including changes of living, sports habits, economics, and patients-request to treatment. We reviewed the literature to describe developments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Two main surgical techniques have been reported to be effective in treating tibial shaft fractures in skeletally immature children: internal fixation (elastic nails and screws) and external fixation. 5 , 6 Screw internal fixation is a suitable option, but is not stable enough to be used alone and requires supplemental long leg cast application. Elastic stable intramedullary nailing (ESIN) has been commonly used since it provides stability, flexible mobility and is usually performed by closed reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Two main surgical techniques have been reported to be effective in treating tibial shaft fractures in skeletally immature children: internal fixation (elastic nails and screws) and external fixation. 5 , 6 Screw internal fixation is a suitable option, but is not stable enough to be used alone and requires supplemental long leg cast application. Elastic stable intramedullary nailing (ESIN) has been commonly used since it provides stability, flexible mobility and is usually performed by closed reduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, close monitoring during follow-up is mandatory, since reduction loss may occur, especially in unstable fracture types. This is also true for other pediatric long bone fractures that are treated non-operatively [10] . After reduction and casting of a long bone fracture, angulation of the fractured segments is measured to determine if the reduction is acceptable.…”
Section: Discussionmentioning
confidence: 95%
“…Now it is clear that the trend of using operative treatment is connected to the perennial trend of considerable sociodemographic and socioeconomic changes in urban societies such as Zagreb. Lifestyle changes directly affect the prevalence of femur fractures among children, and also the approach to treatment choice 48 . Heideken et al showed a 20-year decreasing trend in the prevalence of femur fracture (about three percent annually) in Swedish children 49 .…”
Section: Discussionmentioning
confidence: 99%